Coastal Biodiversity of Tidung Island: Mangrove Forest and Coral Reef Conservation Program - Fauziah Ilmi; Nonon Saribanon; Andri Akbar; Panji B. Surata Aziz; Fauzan Cholifatullah (Journal of Tropical Biodiversity, 2021)
Kepulauan Seribu has different characteristics in the ecosystem from other areas of DKI Jakarta. This area is a group of islands formed by coral reefs and their associations. The different characteristics ecosystem make Kepulauan Seribu increase in tourism and fishery activities. Thus, there is a need for efforts to restore damaged habitats as a result of tourism activities. Restoration of mangroves and coral reefs needs to be carried out to maintain existing natural resources. Based on this background, the research aims to determine the composition and value diversity and evenness of mangrove and coral reefs in Tidung Island. The research was conducted in three locations (Tidung Besar, Tidung Kecil, and Cinta Island) held along in August 2020 & August 2021. The method for vegetation mangrove based by purposive sampling as the representation of the area, with a total of 12 locations spread over the islands, meanwhile in Coral based by LIT (Line Intercept Transect) with a predetermined transect length of 10 meters over the coral reefs. The results of diversity index value successively in Mangrove Forest are 3,429; 1,289, and 3,240. The value of this diversity index is classified as high and medium, increasing more than in 2020. The evenness indexes successively in Mangrove Forest are 0.890; 0.502; and 0.919. The composition of coral genera is 7 genera from 5 Famili. The coral diversity index value is 1.426, which indicates the medium category. The evenness index value of the coral area of Tidung Island is 0.733,which is a high category.